Arctic warming: nonlinear impacts of sea‐ice and glacier melt on seabird foraging. (12th January 2015) - Grémillet, David; Fort, Jérôme; Amélineau, Françoise; Zakharova, Elena; Le Bot, Tangi; Sala, Enric; Gavrilo, Maria
Abstract: Arctic climate change has profound impacts on the cryosphere, notably via shrinking sea‐ice cover and retreating glaciers, and it is essential to evaluate and forecast the ecological consequences of such changes. We studied zooplankton‐feeding little auks ( Alle alle ), a key sentinel species of the Arctic, at their northernmost breeding site in Franz‐Josef Land (80°N), Russian Arctic. We tested the hypothesis that little auks still benefit from pristine arctic environmental conditions in this remote area. To this end, we analysed remote sensing data on sea‐ice and coastal glacier dynamics collected in our study area across 1979–2013. Further, we recorded little auk foraging behaviour using miniature electronic tags attached to the birds in the summer of 2013, and compared it with similar data collected at three localities across the Atlantic Arctic. We also compared current and historical data on Franz‐Josef Land little auk diet, morphometrics and chick growth curves. Our analyses reveal that summer sea‐ice retreated markedly during the last decade, leaving the Franz‐Josef Land archipelago virtually sea‐ice free each summer since 2005. This had a profound impact on little auk foraging, which lost their sea‐ice‐associated prey. Concomitantly, large coastal glaciers retreated rapidly, releasing large volumes of melt water. Zooplankton is stunned by cold and osmotic shock at the boundary between glacier melt and coastal waters, creating new foraging hotspots for little auks. Birds therefore switched from foraging at distant ice‐edge localities, to highly profitable feeding at glacier melt‐water fronts within <5 km of their breeding site. Through this behavioural plasticity, little auks maintained their chick growth rates, but showed a 4% decrease in adult body mass. Our study demonstrates that arctic cryosphere changes may have antagonistic ecological consequences on coastal trophic flow. Such nonlinear responses complicate modelling exercises of current and future polar ecosystem dynamics.